2012
DOI: 10.1152/jn.00615.2011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of synaptic strength vary across an axon arbor

Abstract: Peng X, Parsons TD, Balice-Gordon RJ. Determinants of synaptic strength vary across an axon arbor. J Neurophysiol 107: 2430-2441, 2012. First published January 25, 2012 doi:10.1152/jn.00615.2011.-We used synaptophysin-pHluorin expressed in hippocampal neurons to address how functional properties of terminals, namely, evoked release, total vesicle pool size, and release fraction, vary spatially across individual axon arbors. Consistent with previous reports, over short arbor distances (ϳ100 m), evoked release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…These pools are primed by SNARE complex assembly for rapid synchronous exocytosis in response to action potential-dependent calcium influx (Sudhof, 2013). By contrast, side-by-side comparison of neurons carrying BDNF-pHluorin or a reporter of SVs, synaptophysin (SyP)-pHluotrin (Peng et al, 2012), indicated that secretion of BDNF is asynchronous (Figure 1D–E). The kinetics of BDNF release also drastically differed from transferrin receptor-positive recycling endosomes (Supplemental Figure 2H–J).…”
Section: Resultsmentioning
confidence: 94%
“…These pools are primed by SNARE complex assembly for rapid synchronous exocytosis in response to action potential-dependent calcium influx (Sudhof, 2013). By contrast, side-by-side comparison of neurons carrying BDNF-pHluorin or a reporter of SVs, synaptophysin (SyP)-pHluotrin (Peng et al, 2012), indicated that secretion of BDNF is asynchronous (Figure 1D–E). The kinetics of BDNF release also drastically differed from transferrin receptor-positive recycling endosomes (Supplemental Figure 2H–J).…”
Section: Resultsmentioning
confidence: 94%
“…The identity and activity of the presynaptic cell as well the activation of intracellular signal transduction pathways are factors known to be involved in the regulation of presynaptic vesicle release ( Atwood and Karunanithi, 2002 ; de Jong and Verhage, 2009 ). In a recent study, it was found that terminals formed by the distal part of the axon were stronger compared with proximal synapses, suggesting that presynaptic strength might also depend on the axonal position of a terminal ( Peng et al, 2012 ). Collectively, the observed p r of a given synapse is the result of all the aforementioned determinants and cannot be solely attributed to a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…Randomly selected hippocampal pyramidal neurons, identified by morphology were confocally imaged 18 , 20 (TCS 4D system, Leica Microsystems, Wetzlar, Germany). Images were thresholded automatically using an iterative thresholding technique, 21 and the number and area of individual immunostained pre- or postsynaptic clusters were determined using interactive software (custom-written ImageJ macros).…”
Section: Methodsmentioning
confidence: 99%